Abdominal Cocoon Syndrome After Caustic Ingestion: A Rare Case Report - Doğan, Yusuf; Koc, Mustafa (My University, 2023)
Abdominal cocoon syndrome is a rare condition as etiology of intestinal bowel obstruction. It is a benign cause of small bowel obstruction, and it is termed also encapsulated peritoneal sclerosis (EPS). It can be idiopathic pathology as well as there are many secondary factors like tuberculosis, sarcoidosis, malignancy, drugs, peritoneal dialysis. A 22 years old male without any disease of history, applied to emergency department after caustic ingestion. Direct abdominal radiography, abdomen Ultrasonography (US) and contrast enhanced abdominal Computed Tomography (CT) were performed for patient. The radiography and US were compatible with ileus. The small bowel dilatation with air-fluid leveling, clumping of dilated bowel and peritoneal thickening were seen at abdominal CT. Abdominal cocoon syndrome was thought with this radiologic finding. Eventually surgery proved that this condition with histopathologic examinations. Abdominal cocoon syndrome diagnosis confirmed surgically. We want to share this rare complication of caustic ingestion case with the radiological findings.
Keywords: Genel ve Dahili Tıp; Patoloji; Acil Tıp; Temel Sağlık Hizmetleri; Sağlık Bilimleri ve Hizmetleri